ANALISIS VIDEO PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS V SDN 07 DUNGKAN - Allesandro Welly; Margaretha Lidya Sumarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to analyze the use of interactive learning videos in enhancing the learning interest of fifth-grade students at SDN 07 Dungkan. The research employed a descriptive qualitative approach. The subjects consisted of one fifth-grade teacher and 24 fifth-grade students. Data were collected through observation, interviews, and documentation. The data analysis process involved data reduction, data display, and conclusion drawing. The findings revealed that the use of interactive learning videos contributed positively to students’ learning interest in science and social studies (IPAS). Students demonstrated increased enthusiasm, curiosity, attention, engagement, and participation during the learning process. The visual and audio features presented in the videos helped students understand the learning materials more concretely and meaningfully. Furthermore, the implementation of interactive learning videos encouraged students to become more active in answering questions, participating in discussions, and expressing their opinions. Factors influencing students’ learning interest included internal factors such as motivation, curiosity, and learning readiness, as well as external factors such as teacher support, learning environment, learning facilities, and the use of technology-based instructional media. The study concludes that interactive learning videos can serve as an effective instructional medium to foster students’ learning interest and create a more engaging and meaningful learning experience in elementary schools.